Dada a função f(x) = x²-x, com XER e YER, calcule f(1) + 3f (-1) - 5f (3) + f(0)
Soluções para a tarefa
Respondido por
5
Resposta:
Explicação passo-a-passo:
Dada a função f(x) = x²-x, com XER e YER, calcule
ACHAR
dizendo que:
f(1) ===>(x = 1)
f(x) = x² - x
f(1) = (1)² - 1
f(1) = + 1 - 1
f(1) = 0
e
f(-1) ===>(x = -1)
f(x) = x² - x
f(-1) = (-1)² - (-1))
f(-1) = + 1 + 1
f(-1) = 2
e
f(3) ===>(x = 3)
f(x) = x² - x
f(3) = (3)² - 3
f(3) = 9 - 3
f(3) = 6
e
f(0)===>(x = 0)
f(x) = x² - x
f(0) = (00² - 0
f(0) = 0 - 0
f(0) = 0.
calcule
f(1) + 3f (-1) - 5f (3) + f(0)
0 + 3(2) - 5(6) + 0
+ 6 - 30 = - 24 ( resposta)
Perguntas interessantes